2005
DOI: 10.1007/s10709-005-8693-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of One Intron Loss and Phylogenetic Evolution of Dfak Gene in the Drosophila melanogaster Species Group

Abstract: Intron loss and its evolutionary significance have been noted in Drosophila. The current study provides another example of intron loss within a single-copy Dfak gene in Drosophila. By using polymerase chain reaction (PCR), we amplified about 1.3 kb fragment spanning intron 5-10, located in the position of Tyr kinase (TyK) domain of Dfak gene from Drosophila melanogaster species group, and observed size difference among the amplified DNA fragments from different species. Further sequencing analysis revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Long intron might prevent such an HR. Interestingly, the reported intron exclusion all occur with short intron [16–18]. Interestingly, the introns that are found excluded in this study are generally short except for conifer Adh intron 1 (Fig.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Long intron might prevent such an HR. Interestingly, the reported intron exclusion all occur with short intron [16–18]. Interestingly, the introns that are found excluded in this study are generally short except for conifer Adh intron 1 (Fig.…”
Section: Resultssupporting
confidence: 50%
“…Genome‐wide comparison of intron positions revealed five exact losses of a single internal intron in five genes of mouse, and one such in‐frame loss of an internal intron in rat [16]. Intron Y, which should be located between the intron 7 and 8, was reported to be lost precisely from Dfak of Drosophila melanogaster group [17]. Feiber et al [18] showed that there is an intron presence‐absence polymorphism for the 4f‐rnp gene among Drosophila robusta population in which intron 7 is deleted precisely with the upstream and downstream introns intact.…”
Section: Resultsmentioning
confidence: 99%
“…Formally, the gene replacement event described above represents a case of intron exclusion through cDNA-directed homologous recombination, which has already been described in D. melanogaster [ 64 , 65 ]. Intron exclusion is an important evolutionary process in which homologous recombination events occur between the cDNA generated via retroposition and its genomic, intron-containing locus, resulting in the generation of an intron-free gene.…”
Section: Resultsmentioning
confidence: 99%
“…One of these copies (Dvir\GJ10919) was replaced by a retroposed copy (depicted as C' in Figure 6), whereas the other one (Dvir\GJ22513) retained the structure and possibly the function of the ancestral gene (shown as the structural and functional ortholog in Figure 6). Formally, the gene replacement event described above represents a case of intron exclusion through cDNA-directed homologous recombination, which has already been described in D. melanogaster [64,65]. Intron exclusion is an important evolutionary process in which homologous recombination events occur between the cDNA generated via retroposition and its genomic, intron-containing locus, resulting in the generation of an intron-free gene.…”
Section: V-atpase Gene Duplications In Drosophilidaementioning
confidence: 99%
“…Similar intron losses have been reported in Xy species. For example, a small intron of the Dfak gene is absent from Drosophila melanogaster and D. simulans, but it remains intact in other species of the D. melanogaster species group (Jin et al 2005). Earlier studies by Feiber et al (2002) showed certain intron losses in the 4f-rnp gene in members of a D. melanogaster population.…”
Section: Discussionmentioning
confidence: 99%